Progression-Free Survival and Time to Progression as Potential Surrogate Endpoints for Overall Survival in Chemoradiotherapy Trials in Limited-Stage Small-Cell Lung Cancer: A Systematic Review and Meta-Analysis - Yang, Yin; Wang, Jianyang; Wang, Wenqing; Zhang, Tao; Zhao, Jingjing; Wang, Yu; Li, Yexiong; Wang, Luhua; Bi, Nan (Frontiers in Oncology, 2022)
Purpose To investigate whether progression-free survival (PFS) or time to progression (TTP) could be a valid surrogate endpoint for overall survival (OS) in patients with limited-stage small-cell lung cancer (LS-SCLC) receiving combined chemoradiotherapy. Methods Literature searching was performed in PubMed, Embase, and The Cochrane Library up to 2021. Prediction models were firstly established using data from phase III randomized controlled trials (RCTs) and then externally validated in phase II and retrospective studies. Correlation analysis was evaluated by a weighted linear regression model at both trial and arm levels. Cross-validation was performed to assess the consistency and robustness of the established models. Results 37 studies, including 15 phase III RCTs, 12 phase II studies, and 10 retrospective studies, were selected in the final analysis. In trial-level surrogacy, a very good correlation was observed between hazard ratios (HRs) of PFS/TTP and OS (R2 = 0.783, 95% CI 0.771–0.794). In arm-level surrogacy, very good correlations were also observed between 2-year (R2 = 0.823, 95% CI 0.814–0.832), 3-year (R2 = 0.843, 95% CI 0.833–0.850), 5-year (R2 = 0.852, 95% CI 0.843–0.859) PFS/TTP, and 5-year OS. An excellent correlation was observed between 4-year PFS/TTP and 5-year OS (R2 = 0.906, 95% CI 0.901–0.910). Cross-validation demonstrated reasonable overall consistency. External validation in phase II and retrospective studies showed good agreement (R2, 0.728–0.824). Conclusions PFS/TTP was a valid surrogate endpoint for OS in patients with LS-SCLC receiving combined chemoradiotherapy. The finding provides high-level evidence to support PFS/TTP as the primary endpoint in clinical trials so as to speed up introducing novel agents to the treatment of LS-SCLC.